The Use of Portable Underwater Television in Japan - Nishimura, Minoru; Hara, Masamitsu (The International Hydrographic Review, 2015)
In the past decade underwater television seems to have been widely used all over the world. However this has not been the case in Japan because the underwater optical conditions around Japan are not good, and also because the price of the equipment was so high that potential users could not easily afford it. The recently developed techniques in television and transistors have however stimulated the production of portable and low cost underwater television sets which can be easily applied in the field of oceanographic and fishery research [1], This paper deals with the fundamental features of portable underwater television equipment, its operation in the sea, and some of the results obtained.